Dominus qui incepit ipse perficiat: exhortaciones de fray Josep Mercader a las monjas dominicas del monasterio de Montesión en Barcelona (1740-1745). - LÓPEZ RIBAO, ALEJANDRO JOSÉ (Scripta, 2016)
Among the many interesting people in the eighteenth century at the dominican convent of Santa Catalina virgin and martyr of Barcelona we find fray Josep Mercader (1720-1779). An important paragraph of his works, and also «private», are his eleven exhortations from 1740-1745. They are directed to the dominican nuns of the Montesión monastery in Barcelona on their ceremonies of reception and profession. In these 20 folios we find a discourse between a qualified dominican and the cloistered nuns for the occasion of the two most significant moments of their religious life.